Meso-level simulation of gas hydrate dissociation inlow-permeability sediments - Jianhong Zhang; Chao Zhao; Zhongsheng Xiong (Theoretical and Applied Mechanics Letters, 2014)
This paper presents a meso-level simulation of gas hydrate dissociation in low-permeability marine sediments. Interstitial pores are defined to describe fluid flow and particle movement. The proposed model couples multiphase fluid flow with particle movement to simulate the thermodynamics of gas hydrate dissociation triggered by sharp temperature rises. Hydrates respond quickly to temperature rise in low-permeability sediments. Dissociation causes pore pressure to rise rapidly to equilibrium then steadily increase above equilibrium pressure. Lower permeability sediment builds up greater excess pore pressure as the dissipation of pore pressure is constrained.